2019
DOI: 10.1155/2019/3528148
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-Targeted Transporter-Utilizing Derivatives of Ferulic Acid Can Have Multifunctional Effects Ameliorating Inflammation and Oxidative Stress in the Brain

Abstract: Ferulic acid (FA) is a natural phenolic antioxidant, which can exert also several other beneficial effects to combat neuroinflammation and neurodegenerative diseases, such as Alzheimer's disease. One of these properties is the inhibition of several enzymes and factors, such as β-site amyloid precursor protein (APP) cleaving enzyme 1 (BACE1), cyclooxygenases (COXs), lipoxygenases (LOXs), mammalian (or mechanistic) target for rapamycin (mTOR), and transcription factor NF-κB. We have previously synthesized three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 53 publications
0
17
2
Order By: Relevance
“…One possible reason for high kidney accumulation is another transportation mechanism, which is more prominent for D2. The cellular uptake mechanisms have previously been studied with these two derivatives in vitro . There, we observed that D2 also utilized another non-validated transport mechanism, especially with high concentrations, although the LAT1 was the main transport mechanism for both derivatives with higher affinity.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…One possible reason for high kidney accumulation is another transportation mechanism, which is more prominent for D2. The cellular uptake mechanisms have previously been studied with these two derivatives in vitro . There, we observed that D2 also utilized another non-validated transport mechanism, especially with high concentrations, although the LAT1 was the main transport mechanism for both derivatives with higher affinity.…”
Section: Discussioncontrasting
confidence: 48%
“…17,41 The previous uptake mechanism studies with the FA derivatives have shown that the affinity of D2 toward LAT1 is over 20-times higher when compared to the secondary mechanism, while the overall uptake speed of D2 is 1.5-times faster when compared to D1. 18,42 However, in the present study, with a single high-dose administration, it is possible that other low-affinity transporters along LAT1 are also affecting the distribution of the compounds.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We have also previously reported that LAT1-utilizing derivatives of ferulic acid have multifunctional properties that can ameliorate neuroinflammation and oxidative stress [52]. These included inhibition of BACE1 activity.…”
Section: The Ability Of Perforin Inhibitor and Its Lat1-utilizing Promentioning
confidence: 83%
“…Therefore, the aim of the present study was to identify the possible enzymes responsible for bioconversion of LAT1-utilizing amide prodrugs, particularly in the brain. We have reported that many LAT1-utilizing amide prodrugs are very stable when studied in vitro in tissue homogenates, but they have released their parent drugs in vivo in mice, and curiously some of them selectively in the brain ( Table 1 ) ( Puris et al, 2017 ; Montaser et al, 2019 ; Puris et al, 2019 ). Therefore, it has been hypothesized that the used in vitro assays may lack some essential co-factors required for the optimal function of the bioconverting enzymes.…”
Section: Introductionmentioning
confidence: 99%